In Vitro Characterization of Motor Neurons and Purkinje Cells Differentiated from Induced Pluripotent Stem Cells Generated from Patients with Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay. (15th April 2023) - Louit, Aurélie; Beaudet, Marie-Josée; Blais, Mathieu; Gros-Louis, François; Dupré, Nicolas; Berthod, François
Abstract : Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is an early-onset neurodegenerative disease mainly characterized by spasticity in the lower limbs and poor muscle control. The disease is caused by mutations in the SACS gene leading in most cases to a loss of function of the sacsin protein, which is highly expressed in motor neurons and Purkinje cells. To investigate the impact of the mutated sacsin protein in these cells in vitro, induced pluripotent stem cell- (iPSC-) derived motor neurons and iPSC-derived Purkinje cells were generated from three ARSACS patients. Both types of iPSC-derived neurons expressed the characteristic neuronal markers β 3-tubulin, neurofilaments M and H, as well as specific markers like Islet-1 for motor neurons, and parvalbumin or calbindin for Purkinje cells. Compared to controls, iPSC-derived mutated SACS neurons expressed lower amounts of sacsin. In addition, characteristic neurofilament aggregates were detected along the neurites of both iPSC-derived neurons. These results indicate that it is possible to recapitulate in vitro, at least in part, the ARSACS pathological signature in vitro using patient-derived motor neurons and Purkinje cells differentiated from iPSCs. Such an in vitro personalized model of the disease could be useful for the screening of new drugs for the treatment of ARSACS.